Express determination of iron microimpurities in technological solutions for growing KH₂PO₄ single crystals by visual test meth - Ivkova, T.I.; Pantaler, R.P.; Blank, A.B.; Reshetnyak, E.A.; Vakhovskaya, Yu.Eu. (Functional Materials, 2004)
Studied are the conditions for express determination of microamounts of iron with 4,7-diphenyl-1,10-phenanthroline (bathophenanthroline) in the form of ionic associate (IA) with NO3_ ions. A technique is proposed for pumping sorption of the IA from the solution by means of polyurethane foam. The statistically calculated lower limit of the determined Fe (II, III) contents in the "unreliable reaction" region is 0.03 pg/ml, the determination time does not exceed 10 min, the relative standard deviation of the determination of 0.03 to 0.20 pg/ml of Fe (II, III) is 0.36 and 0.21, respectively (n = 30). The developed test is used for express visual determination of iron (II, III) at the level of 5 -10 5 % in the mother liquid for potassium dihydrogen phosphate crystal growth. Изучены условия экспрессного определения микропримесей железа с 4,7-дифенил-1,10-фенантролином (батофенантролином) в виде ионного ассоциата (ИА) с Ю3_-иона-ми. Предложен способ прессингового извлечения ИА из раствора пенополиуретаном. Статистически рассчитанный нижний предел обнаружения Fe (II,III) для области "ненадёжной реакции" составляет 0,03 мкг/мл. Время определения не превышает 10 мин., относительное стандартное отклонение при определении от 0.03 до 0.2 мкг/мл составляет 0.36-0.21 (n = 30), соответственно. Предлагаемый тест был применён для определения суммарного содержания Fe (II,III) на уровне 5-10-5 % в технологических растворах для выращивания монокристаллов KH2PO4. Вивчено умови експресного визначення мікродомішок заліза з 4,7-дифеніл 1,10-фе-нантроліном (батофенантроліном) у вигляді іоного асоціату (IA) з Ю3--іонами. Запропоновано пресінговий спосіб вилучення IA з розчину пінополіуретановим сорбентом. Статистично розрахована нижня межа визначення Fe (II,III) у області "ненадійної реакції" дорівнює 0.03 мкг/мл, відносне стандартне відхилення при визначенні від 0.03 до 0.2 мкг/мл дорівнює 0.36-0.21 (n = 10), відповідно, час визначення не перевищує 10 хвилин. Запропонований тест було застосовано для визначення сумарного вмісту Fe (II,III) на рівні 5-10-5 % у технологічних розчинах для ви рощування монокристалів KH2PO4.